The enlightenment of fiction: Literature to learn to philosophise - Edwige Chirouter (Journal of Philosophy in Schools)
This article summarises nearly 20 years of academic research into the links between children, literature and philosophy. The democratisation of philosophy teaching is critical today in a world characterised by complexity and by crises on many fronts. For Martha Nussbaum, the trend in the global education system is to sideline the humanities in favour of a dehumanised, purely technological approach to knowledge, thereby paving the way for a serious crisis of democracy. Yet the humanities offer the only way for future citizens to develop their reasoning skills, sensitivity, critical faculties, and empathy. The challenge facing this alliance between philosophy (with children) and literature (for young people) is, therefore, profoundly political: to train enlightened citizens informed by fiction. Stories (picturebooks and novels) embody the potential for a multitude of exemplary and meaningful experiences of the truth(s) of the world, and as such constitute an autonomous space for thinking. Literature is, therefore, an authentic experience, both specific and universal, through which readers can grasp reality. It is an immense laboratory in which we can, at any age, rework the situations, dilemmas and problems that affect humanity. Free from the constraints of empirical reality, the laws of physics, and the laws of morality, fiction allows us to experience by proxy what we will never actually experience in the real world. Fiction creates a healthy emotional distance, making it easier to think deeply and rigorously. The article summarises the conclusions reached about the principles and role of (children’s) literature in early learning about philosophy.